The Clinical Characteristics of ARDS in Children With Hematological Neoplasms - Zhang, Qiao; Hu, Wen-ting; Yin, Fan; Qian, Han; Wang, Ying; Li, Bi-ru; Qian, Juan; Tang, Yan-jing; Ning, Bo-tao (Frontiers in Pediatrics, 2021)
In order to explore the clinical characteristics of pediatric patients admitted to pediatric intensive care unit (PICU), who suffer from hematological neoplasms complicated with acute respiratory distress syndrome (ARDS), we retrospectively analyzed 45 ARDS children with hematological neoplasms, who were admitted to the PICU of Shanghai Children's Medical Center from January 1, 2014 to December 31, 2020. The 45 children were divided into survival group and death group, pulmonary ARDS group and exogenous pulmonary ARDS group, agranulocytosis group and non-agranulocytosis group, respectively, for statistical analysis. The male to female ratio was about 1.4:1, and the median age was 4 years old. The main clinical manifestations were fever, cough, progressive dyspnea and hypoxemia. 55.6% (25/45) of the children had multiple organ dysfunction syndrome (MODS). The overall mortality rate was 55.6% (25/45). The vasoactive inotropic score (VIS), pediatric critical illness scoring(PCIS) , average fluid volume in the first 3 days and the first 7 days, the incidence of MODS in the death group were all significantly higher than those in the survival group (P<0.05). However, total length of mechanical ventilation, total hospital stay and length of PICU days in the death group were significantly lower than those in the survival group (P<0.05). The PCIS (OR=0.832, P=0.004) and the average fluid load in the first 3 days (OR=1.092, P=0.025) were independent risk factors for predicting death. Children with exogenous pulmonary ARDS were more likely to have MODS than pulmonary ARDS (P<0.05). The mean values of VIS、C reactive protein(CRP) and procalcitonin(PCT) in children with exogenous pulmonary ARDS were also higher (P < 0.05). The total length of hospital stay、peak inspiratory pressure(PIP)、VIS、 CRP and PCT in agranulocytosis group were significantly higher than those in non-agranulocytosis group (P<0.05). In conclusion, children with hematologic neoplasms complicated with ARDS had a high overall mortality and poor prognosis. Children complicated with MODS, positive fluid balance, high VIS and PCIS scores were positively correlated with mortality. Especially，PCIS score and average liquid load in the first 3 days were independent risk factors for predicting death. Children with exogenous pulmonary ARDS and children with agranulocytosis were more critically ill.